LENGTH WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR OF INDIAN SHAD, TENUALOSA ILISHA FROM HOOGHLY ESTUARY SYSTEM, WEST BENGAL - SARKAR, SUDIPTA; DAS, SUDHIR KUMAR; BHAKTA, DIBAKAR (Journal of the Inland Fisheries Society of India, 2021)
The study on the length weight relationship (LWR) and relative condition factor (Kn) of Indian Shad (Tenualosa ilisha) was conducted for a period of seven months (June to December, 2013) from Diamond Harbour area of Hooghlyestuarine system, West Bengal. During the period of investigation, 245 samples of unsexed Tenualosa ilisha having length of 210 to 420 mm and body weight of 115 to 775 g were examined. The LWR found for Tenualosa ilisha was W= 0.0000206 L 2.817 for pooled samples. The correlation coefficient of 0.892 between length and weight was significant (P